2018
DOI: 10.1049/iet-cds.2017.0427
|View full text |Cite
|
Sign up to set email alerts
|

Spintronic memristor synapse and its RWC learning algorithm

Abstract: As one of the most widely used memristor models, the spintronic memristor has become a promising candidate for the electronic synapse. Non-volatility, nanoscale geometries, binary data and multi-level information storage make the circuit simpler and consume less electricity. In this study, a new spintronic memristor synaptic circuit is proposed which can realise positive, zero and negative weights successfully. Furthermore, the circuits of the presented synaptic-based neuron and compact neural network are desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Chen et al designed a synaptic circuit composed of three memristors and two transistors [26], as shown in Figure 4. The input voltage is V in , and the output V out is the voltage difference between A and B.…”
Section: Other Digital Synaptic Structuresmentioning
confidence: 99%
“…Chen et al designed a synaptic circuit composed of three memristors and two transistors [26], as shown in Figure 4. The input voltage is V in , and the output V out is the voltage difference between A and B.…”
Section: Other Digital Synaptic Structuresmentioning
confidence: 99%
“…In addition, the memristive function of DW motion in a MTJ by experiments was verified. , By resolving the Landau-Lifshitz-Gilbert equation with STT, Huang et al put forward a spintronic memristor based on the magnetic Skyrmion number to represent analog information, as shown in Figure c, which is another concept of the spintronic memristors Figure d–g shows the simulation diagram of the spintronic memristor Figure d presents the relationship between the input square wave voltage and time, and the I – V curve was obtained under applied voltage (Figure e).…”
Section: Introductionmentioning
confidence: 99%
“…58 Figure 3d−g shows the simulation diagram of the spintronic memristor. 59 Figure 3d presents the relationship between the input square wave voltage and time, and the I−V curve was obtained under applied voltage (Figure 3e). By analyzing the change of memristor, it can be concluded that when the voltage was applied to the spintronic memristor and reached a certain level, the resistance state will be changed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various memristor synaptic circuit methods have been designed, such as learning algorithms and associative learning algorithms. [8,9] In this case, it is of great significance to establish a good memristor application research model.…”
Section: Introductionmentioning
confidence: 99%